Implementasi Program Literasi Keagamaan dalam Upaya Peningkatan Prestasi Belajar Aqidah Akhlak di MTs Negeri 5 Pasaman Barat pada Masa Covid-19 - Desma Desma (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
To maintain the quality of learning outcomes in the Covid-19 period, creativity and innovation from teachers, because activities that can usually be done directly must be transferred online, without exception in teaching and learning activities. Teachers in MTs Negeri 5 Pasaman Barat have innovation by fulfilling Islamic literature both online and available in schools. In line with this reality, this study aims to describe how religious literacy programs are implemented as an effort to improve the learning outcomes of Aqidah Akhlak during the Covid-19 period in MTs Negeri 5 West Pasaman. To achieve the purpose of this research, the approach used is qualitative, data collection techniques are carried out with observations, interviews and documentation studies. The result of the study is that first, teacher Aqidah Akhlak and Head of State MTs 5 fulfill Islamic literature in the library that can be accessed by students offline. Guru Aqidah Akhlak also provides online Islamic literature that can be accessed by online learners, either through whatsApp groups, teacher rooms and online links prepared. Second, the availability of Islamic literature both in Madrasah and online makes the learning results of Aqidah Akhlak in MTs Negeri 5 Pasaman Barat maintained.